Criterion Validity of the Implicit Positive and Negative Affect Test: Prediction of Facial Affect Perception - Weil, Anna-Sophie; Günther, Vivien; Schmidt, Frank Martin; Kersting, Anette; Quirin, Markus; Suslow, Thomas (Frontiers in Psychology, 2021)
The present study focused on the criterion-related validity of the Implicit Positive and Negative Affect Test (IPANAT). The IPANAT is thought to be a measure of automatic activation of cognitive representations of affects. Here it was investigated whether implicit affect scores differentially predict ratings of facial emotions over and above explicit affectivity. Ninety-six young female participants completed the IPANAT, the Positive and Negative Affect Schedule (PANAS) as an explicit measure of state and trait affectivity, and a task for the perception of facial emotions. Implicit negative affect predicted the perception of negative but not positive facial emotions, whereas implicit positive affect predicted the perception of positive but not negative facial emotions. The observed double-dissociation in the correlational pattern strongly supports the validity of the IPANAT as a measure of implicit affectivity and is indicative of the orthogonality and thus functional distinctness of the two affect dimensions of the IPANAT. Moreover, such affect-congruent correlations were absent for explicit affect scales, which additionally supports incremental validity of the IPANAT.